An investigation into syntactic and phonetic devices used in english advertising slogans - Trần Thị Thanh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Examining the syntactic and phonetic devices used in English advertising slogans; Providing students and teachers with practical knowledge to recognize and analyze the syntactic and phonetic devices used in English advertising slogans